(untitled) (مجلة الواحات للبحوث والدراسات, 2020)
Algerian Scientists Have Had Contributions To Various Useful Sciences, Including The Various Sciences Of The Qur’an, And This Research Shows The Efforts Of Algerian Scientists To Serve An Important Science Related To The Holy Qur’an, Which Is The Strange Of The Holy Qur’an, In The Late Centuries. And The Algerians Have Long Been Concerned With The Holy Qur’an, Preoccupied With Its Sciences From An Ancient Time, And They Had A Share In Serving The Sciences Related To The Great Qur’an, Including Its Strange Ones, And This Is Evident Through The Scientific Legacy Our Scholars Have Left In This Art. This Research Showed Those Scientists Who Served The Science Of The Stranger A Great Service, Through The Authorship, Prose And Explanation, So The Author Of The Research Highlighted These Efforts Through Brief Translations Of These Flags, As Well As Identifying Their Works, And Showing Their Method Of Authorship. Key Words ـ Strange Qur’an, Algerian Scholars, Efforts